Toxics of Tobacco Smoke and Cardiovascular System: From Functional to Cellular Damage - Leone, Aurelio (Current Pharmaceutical Design, 2015)
Manufactured tobacco contains over 4, 000 toxic substances, but only a few exert adverse cardiovascular effects. Nicotine and its metabolites, carbon monoxide, thiocyanate and some aromatic amines play a strong, although different, role to determine cardiovascular damage. Of these substances, however, nicotine, acting by the double mechanism of addiction and receptor-binding, and carbon monoxide by increasing the production of carboxyhemoglobin and hypoxia, are the main determinants of the damage. The development of the alterations of heart and blood vessels follows a typical way, initially consisting of functional responses that become irreversible pathological lesions at the time. Myocardium and endothelial cells are the targets where cigarette smoking exerts its effects. The first displays functional and pathological disorders primarily related to ischemic heart disease, cardiomyopathy, including experimental cardiomyopathy from smoking, and heart failure, while the second should be interpreted as a structure, which shows early alterations caused by smoking as clearly evident, repeatable and typically depending on smoking toxicity. Cardiovascular damage has a functional onset, which, at the time, leads to irreversible morphological damage of myocardial and endothelial cells.
Keywords: functional damage